Sleep duration and mortality – Does weekend sleep matter? - Åkerstedt, Torbjörn (J Sleep Res, 2018)
Previous studies have found a U‐shaped relationship between mortality and (weekday) sleep duration. We here address the association of both weekday and weekend sleep duration with overall mortality. A cohort of 43,880 subjects was followed for 13 years through record‐linkages. Cox proportional hazards regression models with attained age as time‐scale were fitted to estimate multivariable‐adjusted hazard ratios and 95% confidence intervals for mortality; stratified analyses on age (<65 years, ≥65 years) were conducted. Among individuals <65 years old, short sleep (≤5 hr) during weekends at baseline was associated with a 52% higher mortality rate (hazard ratios 1.52; 95% confidence intervals 1.15–2.02) compared with the reference group (7 hr), while no association was observed for long (≥9 hr) weekend sleep. When, instead, different combinations of weekday and weekend sleep durations were analysed, we observed a detrimental association with consistently sleeping ≤5 hr (hazard ratios 1.65; 95% confidence intervals 1.22–2.23) or ≥8 hr (hazard ratios 1.25; 95% confidence intervals 1.05–1.50), compared with consistently sleeping 6–7 hr per day (reference). The mortality rate among participants with short sleep during weekdays, but long sleep during weekends, did not differ from the rate of the reference group. Among individuals ≥65 years old, no association between weekend sleep or weekday/weekend sleep durations and mortality was observed. In conclusion, short, but not long, weekend sleep was associated with an increased mortality in subjects <65 years. In the same age group, short sleep (or long sleep) on both weekdays and weekend showed increased mortality. Possibly, long weekend sleep may compensate for short weekday sleep.